2016
DOI: 10.1038/ncomms13277
|View full text |Cite
|
Sign up to set email alerts
|

Splenic differentiation and emergence of CCR5+CXCL9+CXCL10+ monocyte-derived dendritic cells in the brain during cerebral malaria

Abstract: Dendritic cells have an important role in immune surveillance. After being exposed to microbial components, they migrate to secondary lymphoid organs and activate T lymphocytes. Here we show that during mouse malaria, splenic inflammatory monocytes differentiate into monocyte-derived dendritic cells (MO-DCs), which are CD11b+F4/80+CD11c+MHCIIhighDC-SIGNhighLy6c+ and express high levels of CCR5, CXCL9 and CXCL10 (CCR5+CXCL9/10+ MO-DCs). We propose that malaria-induced splenic MO-DCs take a reverse migratory rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 69 publications
3
66
0
Order By: Relevance
“…Previous studies have shown that CXCL9 and CXCL10 can be secreted by multiple cell types including monocytes, endothelial cells, fibroblasts, inflammatory macrophages dendritic cells (particularly the cDC1 subtype) and tumor cells themselves (9,12,13,(66)(67)(68). In the context of cancer, previous data have suggested that tumor cells (68), CD103 þ DCs (9, 12, 69), or CD11b þ cells (67) are major sources of CXCL9/10 within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CXCL9 and CXCL10 can be secreted by multiple cell types including monocytes, endothelial cells, fibroblasts, inflammatory macrophages dendritic cells (particularly the cDC1 subtype) and tumor cells themselves (9,12,13,(66)(67)(68). In the context of cancer, previous data have suggested that tumor cells (68), CD103 þ DCs (9, 12, 69), or CD11b þ cells (67) are major sources of CXCL9/10 within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid cells that include monocytes and monocyte-derived DCs have indeed been reported to be major producers of CXCL9 and CXCL10 in the inflamed brain (27). Recent studies indicate that CCR2 + myeloid cells precede CD4 + T cell infiltration in the heart in response to TAC, and their depletion results in impaired CD4 + T cell expansion in the mLNs and subsequent recruitment to the heart (40,41). Our data, in line with these studies, demonstrate that a high percentage of CCR2 + -recruited monocytes and macrophages are indeed a source of CXCL10 and that CCR2 + macrophages also produce CXCL9.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Mo-DCs have been recently shown to be one of the major CXCL9/10 producers in the spleen during the development of ECM. These cells were shown to traffic to the brain in a CCR5-dependent manner, possibly also contributing to the induction of T cell trafficking to the brain during the development of ECM by acting as early sources of CXCL9 and CXCL10 (69). Here, we have shown that there exists a population of iMOs and Mo-DCs firmly adhered to the lumen of the brain postcapillary venules, which produce high levels of both CXCL9 and -10 that are, in combination with EC-produced CXCL10, activating CXCR3 on the T cells in the blood and thus contributing to T cell-EC interactions within the brain during CM.…”
Section: Discussionmentioning
confidence: 99%